Methods for quantifying Staphylococcus aureus in indoor air. (21st June 2014) - Chang, C.‐W.; Wang, L.‐J.
Abstract Staphylococcus aureus has been detected in indoor air and linked to human infection. Quantifying S. aureus by efficient sampling methods followed by appropriate sample storage treatments is essential to characterize the exposure risk of humans. This laboratory study evaluated the effects of sampler type (all‐glass impinger (AGI‐30), BioSampler, and Andersen one‐stage sampler (Andersen 1‐STG)), collection fluid (deionized water (DW), phosphate‐buffered saline (PBS), and Tween mixture (TM)), and sampling time (3–60 min) on cell recovery. Effects of storage settings on bacterial concentration were also assessed over 48 h. Results showed BioSampler performed better than Andersen 1‐STG and AGI‐30 (P < 0.05) and TM was superior to PBS and DW (P < 0.05). An increase in sampling time negatively affected the recoveries of cells in PBS of BioSampler and AGI‐30 (P < 0.05), whereas cell recoveries in TM were increased at sampling of 6–15 min compared with 3 min. Concentrations of cells collected in PBS were decreased with storage time at 4 and 23°C (P < 0.05), while cells stored in TM showed stable concentrations at 4°C (P > 0.05) and increased cell counts at 23°C (P < 0.05). Overall, sampling by BioSampler with TM followed by sample transportation and storage at 4°C is recommended.